1998
DOI: 10.1128/iai.66.5.2143-2153.1998
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Immunity againstBorrelia burgdorferiDecorin Binding Protein A (DbpA) Protects against Infection

Abstract: Borrelia burgdorferi, the spirochete that causes Lyme disease, binds decorin, a collagen-associated extracellular matrix proteoglycan found in the skin (the site of entry for the spirochete) and in many other tissues. Two borrelial adhesins that recognize this proteoglycan, decorin binding proteins A and B (DbpA and DbpB, respectively), have recently been identified. Infection of mice by low-dose B. burgdorferi challenge elicited antibodies against DbpA and DbpB that were sustained at high levels, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 57 publications
4
84
0
Order By: Relevance
“…Many of the individual purified proteins tested as vaccines do not confer complete protection (Hanson et al, 1998;Exner et al, 2000;Hagman et al, 2000;Nogueira et al, 2012;Floden et al, 2013). Passive transfer of serum from mice (or humans) injected with WT bacteria or with certain B. burgdorferi proteins seems to provide limited protection (Fikrig et al, 1994;Barthold et al, 1997;Hanson et al, 1998;Fikrig et al, 2000;Hagman et al, 2000;Floden et al, 2013;Small et al, 2014), suggesting that antibodies can provide protection if generated against critical antigens. Attenuated or killed vaccines have been successful in preventing many bacterial and viral infections (Mc, 1948;Mekalanos, 1994;Jin and Subbarao, 2015), but there are few studies screening non-infectious B. burgdorferi mutants for potential protective abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the individual purified proteins tested as vaccines do not confer complete protection (Hanson et al, 1998;Exner et al, 2000;Hagman et al, 2000;Nogueira et al, 2012;Floden et al, 2013). Passive transfer of serum from mice (or humans) injected with WT bacteria or with certain B. burgdorferi proteins seems to provide limited protection (Fikrig et al, 1994;Barthold et al, 1997;Hanson et al, 1998;Fikrig et al, 2000;Hagman et al, 2000;Floden et al, 2013;Small et al, 2014), suggesting that antibodies can provide protection if generated against critical antigens. Attenuated or killed vaccines have been successful in preventing many bacterial and viral infections (Mc, 1948;Mekalanos, 1994;Jin and Subbarao, 2015), but there are few studies screening non-infectious B. burgdorferi mutants for potential protective abilities.…”
Section: Discussionmentioning
confidence: 99%
“…If decorin binding is an early step in pathogenesis, Dbps would be excellent targets for vaccine development. Indeed, vaccine studies using Dbps demonstrated that mice passively or actively vaccinated with DbpA are protected when challenged with pathogenic B. burgdorferi (Hanson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…After labelling, the grids were washed briefly in three changes of deionized water and negatively stained in 0.5% ammonium molybdate. The samples were examined on a Hitachi HU-11 E transmission electron microscope operated at 75 kV (Hanson et al, 1998).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Two borrelial proteins, decorin-binding proteins A and B (DbpA and DbpB), have been shown to bind host decorin (Guo et al, 1995). Decorin is a proteoglycan that FEMS Immunol Med Microbiol 66 (2012) Hagman et al, 1998;Hanson et al, 1998). Both proteins are upregulated on the surface of B. burgdorferi organisms grown at reduced pH and by a temperature shift from 23 to 37°C, which suggests an important role for these proteins in the mammalian environment Revel et al, 2002;Ojaimi et al, 2003).…”
Section: Dbpa and Dbpbmentioning
confidence: 99%